BIAYA KUALITAS DAN KOMPQNENNYA PADA BAD AN USAHA PERAIH ISO 9000 DI KAWASAN INDUSTRI SIER DAN PIER - Stefanus Budy Widjaja Subali; Yie Ke Feliana (Journal of Management and Business, 2005)
Quality has become an important competitive dimension for all organization. Recently, -the emphasis on quality has shifted from a source of strategic advantage to a compepetive necessity As the companies implement quality-improvement programs,one of those is. ISO 9000, a need arises to monitor and report on the progress of these programs. Managers r need to know about the quality costs and the component of quality costs. The component of quality costs include prevention, appraisal, internal failure and external failure costs. This article describes how the companies that were awarded ISO 9000 define the quality costs, what items to be included in the each component of quality costs and how the composition of each component of quality activity cost driver is.